2012
DOI: 10.1111/j.1365-2133.2012.11125.x
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma incidence and mortality in Europe: new estimates, persistent disparities

Abstract: The most recent estimates of melanoma incidence and mortality in Europe reveal sharp differences between European countries, possibly related to missed opportunities for early diagnosis and incomplete reporting of melanoma in Eastern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
1
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(168 citation statements)
references
References 24 publications
(64 reference statements)
7
145
1
15
Order By: Relevance
“…Stratification of 103 patients with invasive melanoma in this study by staging and Clark invasion level showed that the major part of patients were diagnosed on (Azarjana et al, 2012), 2.7 in men and 3.5 in females in Belarus, 4.4 in men and 4.6 in females in Poland (Curado et al, 2007). Being in agreement with a recent research, this observation showed melanoma incidence rates to vary considerably within European countries with the highest rates in Switzerland (19.2/100.000) (Forsea et al, 2012). With regard to genders, the melanoma incidence rates were identical for the analyzed period.…”
Section: Resultssupporting
confidence: 78%
“…Stratification of 103 patients with invasive melanoma in this study by staging and Clark invasion level showed that the major part of patients were diagnosed on (Azarjana et al, 2012), 2.7 in men and 3.5 in females in Belarus, 4.4 in men and 4.6 in females in Poland (Curado et al, 2007). Being in agreement with a recent research, this observation showed melanoma incidence rates to vary considerably within European countries with the highest rates in Switzerland (19.2/100.000) (Forsea et al, 2012). With regard to genders, the melanoma incidence rates were identical for the analyzed period.…”
Section: Resultssupporting
confidence: 78%
“…A tanulmány alapján a kelet-közép-európai országokban Észak-és Nyugat-Európához képest az alacsonyabb incidenciához hátrányosabb stádium szerinti megoszlás és magasabb mortalitás társul. Az Egyesült Államokban, Ausztráliában, Nyugat-Európában tapasztalt kedvezőbb megoszlásnak számos oka lehet, amelyek közül Forsea és munkatársai kiemelik a betegek felvilágosításában, az egészségügyi oktatásban, az országos rákregiszterekben, a rizikófaktorokban, az orvosi ellátásban fennálló különbségeket [20].…”
Section: Megbeszélésunclassified
“…Reported incidence is highest in Switzerland (25/100,000 per year), Denmark, Norway and the Netherlands, and lowest in Central Eastern European (CEE) countries including Albania, Greece and Romania (below 4/100,000 per year). While the highest mortality rate was in Norway, and the lowest in Greece, CEE countries have the largest share of deaths (35.5%) of the 4 European regions (Forsea et al, 2012). A paper that calculated mortality-to-incidence ratio (MIR) for European countries for melanoma as a proxy for the fatality rate showed it ranges between 0.09 in Switzerland and 0.44 in Latvia.…”
Section: Melanoma: Key Facts and Challengesmentioning
confidence: 99%